Transmedia, Translation and Adaptation: Parallel Universes or Complex System? - Canalès, Audrey (TTR)

(untitled) (Association canadienne de traductologie, 2020)
This article explores the relationship between transmedia narratives, translation, and adaptation, and exposes why one can be lead to believe that these disciplines have very little in common. It first gives a definition of complexity and transmedia narratives, and explains the difference between transmedia, crossmedia, and multimedia. It then describes the types of transmedia projects proposed by Christy Dena (2011, n.p.) and illustrates them with the examples of two cult series’ narrative universes, that is, Twin Peaks and Skam. Transmedia stories, which spread on multiple platforms and involve audience participation, are considered by transmedia theorists to be part of story worlds (story universes, or “storyverses”). Yet, most of these narratives can be considered as adaptations, or as multimodal, intersemiotic translations. Despite the evident relationship between translation, adaptation and transmedia, adaptation is reduced to a mere media transfer, and translation is mostly referred to as an interlinguistic operation in recent academic conversations around transmedia and participatory culture. This article examines how the emergence of transmedia narratives illuminates the fact that adaptation and translation must step into the study of contemporary transmedial landscape, and how transmedia, translation and adaptation could gain from it.